2019
DOI: 10.1007/s00442-019-04371-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental drought reduces genetic diversity in the grassland foundation species Bouteloua eriopoda

Abstract: Understanding the resistance and resilience of foundation plant species to climate change is a critical issue because the loss of these species would fundamentally reshape communities and ecosystem processes. High levels of population genetic diversity may buffer foundation species against climate disruptions, but the strong selective pressures associated with climatic shifts may also rapidly reduce such diversity. We characterized genetic diversity and its responsiveness to experimental drought in the foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 96 publications
0
14
2
Order By: Relevance
“…Therefore, plant-soil feedback driven changes in population structure may magnify the negative effect of drought on P. virgatum productivity. While previous work has found that drought may cause rapid evolutionary change in a foundational grass (Whitney et al 2019), the genotype-dependent soil legacies we found suggest that precipitation and soil microbes jointly drive evolution in P. virgatum populations. Subsequent changes in the microbial community caused by microbially driven changes in P. virgatum populations sets up the potential for strong ecoevolutionary dynamics in this system.…”
Section: Fig 1 Variation In Plant-soil Feedback Amongcontrasting
confidence: 79%
“…Therefore, plant-soil feedback driven changes in population structure may magnify the negative effect of drought on P. virgatum productivity. While previous work has found that drought may cause rapid evolutionary change in a foundational grass (Whitney et al 2019), the genotype-dependent soil legacies we found suggest that precipitation and soil microbes jointly drive evolution in P. virgatum populations. Subsequent changes in the microbial community caused by microbially driven changes in P. virgatum populations sets up the potential for strong ecoevolutionary dynamics in this system.…”
Section: Fig 1 Variation In Plant-soil Feedback Amongcontrasting
confidence: 79%
“…For each site, all plots within a block (including the control) were located at least 5 m apart, and trenched to 20 cm and surrounded by an aluminum flashing barrier to hydrologically isolate them from the adjacent soil. The most significant environmental artifacts of these shelters are a 0.4°C increase in temperature (Whitney et al, 2019), and 5%-10% reduction in light due to the polycarbonate roofing material used, which is still above saturating light levels in this system.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, these valuable genetic resources are found to be highly underconserved (18), and concerns for losing these genetic resources are mounting (19). Also, many studies have revealed increasing threats for crop wild relatives in natural populations, particularly from global warming (1, 20, 21), but few studies have characterized genetic responses of wild relative populations to the threats of global warming (22–24).…”
mentioning
confidence: 99%